KONTESTASI BAHASA PADA PAPAN NAMA USAHA DI KOTA BANDAR LAMPUNG - Renita Sekar Lupito; Suhandano (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
The use of Indonesian, regional languages ​​and foreign languages ​​on business signs in Bandar Lampung shows language contestation. This language contest involves 14 languages, of these 14 languages ​​there are languages ​​that are dominant and those that are not. This research aims to map and analyze language distribution and describe language contestation through language use patterns that appear on business signboards. The observation method using photography techniques was used to collect data. A total of 300 photos of business nameplates along the main roads in 4 sub-districts (Teluk Betung Selatan, Teluk Betung Timur, Teluk Betung Utara, and Teluk Betung Barat) were taken as research objects. First, the data is grouped based on the pattern (monolingual, bilingual, and multilingual) then the grouped patterns are analyzed based on the type of business. Second, we look at the use of Lampung language for types of business. Research findings show that Indonesian is more dominant than other languages ​​in monolingual and bilingual patterns, while in multilingual patterns Indonesian takes precedence over English. For the Lampung language, although it only appears on a handful of business boards, local identity still appears, especially in typical food and clothing businesses and in the names of tourist attractions. The social implication of this research is that the people of Lampung still have the awareness to preserve and reflect Lampung's cultural identity through the businesses they build.